In vitro–In vivo Hybrid Approach for Studying Modulation of NRF2 in Immortalized Bovine Mammary Cells - Ford, Hunter R.; Busato, Sebastiano; Bionaz, Massimo (Frontiers in Animal Science, 2021)
Nuclear factor erythroid 2-related factor 2 (NRF2) plays a key role in the response to oxidative stress. Diets containing known NRF2 modulators could be used to minimize oxidative stress in dairy cows. Currently, studies evaluating the activity of NRF2 in bovine have used the classical in vitro approach using synthetic media, which is very different than in vivo conditions. Furthermore, studies carried out in vivo cannot capture the short-term and dynamic response of NRF2. Thus, there is a need to develop new approaches to study NRF2 modulation. The aim of the present study was to establish an in vitro-in vivo hybrid system to investigate activation of NRF2 in bovine cells that can serve as an intermediate model with results closer to what is expected in vivo. To accomplish the aim, we used a combination of a gene reporter assay in immortalized bovine mammary cells, synthetic NRF2 modulators, and blood serum from periparturient cows. Synthetic agonist tert-butylhydroquinone and sulforaphane confirmed to be effective activators of bovine NRF2 with acute and large effect at 30 and 5 μM, respectively, with null response after the above doses due to cytotoxicity. When the agonists were added to blood serum the response was more linear with maximum activation of NRF2 at 100 and 30 μM, respectively, and the cytotoxicity was prevented. High concentration of albumin in blood serum plays an important role in such an effect. Brusatol (100 nM) was observed to be an effective NRF2 inhibitor while also displaying general protein synthesis inhibition and cytotoxicity when added to synthetic media. A consistent inhibition of NRF2 was observed when brusatol was added to the blood serum but the cytotoxicity was reduced. The synthetic inhibitor ML385 had no effect on modulation of bovine NRF2. Hydrogen peroxide activates NRF2 in bovine mammary cells starting from 100 μM; however, strong cytotoxicity was detected starting at 250 μM when cells were cultivated in the synthetic media, while blood serum prevented cytotoxicity. Overall, our data indicated that the use of synthetic media can be misleading in the study of NRF2 in bovine and the use of blood serum appears necessary.